Clinical Implications of Helicobacter pylori Antibiotic Resistance in Italy: A Review of the Literature - Enrico Celestino Nista; Antonio Pellegrino; Lucia Giuli; Marcello Candelli; Tommaso Schepis; Sara Sofia De Lucia; Veronica Ojetti; Francesco Franceschi; Antonio Gasbarrini (Antibiotics, 2022)
Helicobacter pylori (H. pylori) resistance to antibiotics has increased worldwide in recent decades, especially to clarithromycin. As a result, the World Health Organization (WHO) identified clarithromycin-resistant H. pylori as a “high priority” pathogen in 2017. As international guidelines recommend empirical therapy as first-line treatment, it is crucial to know local resistance rates and history of antibiotic use to determine the most appropriate first-line antibiotic treatment. Italy is one of the European countries with the highest prevalence of H. pylori infection and the highest percentage of antibiotic-resistant H. pylori. The aim of this review is to summarize all data on H. pylori antibiotic resistance in Italy in order to quantify the current rate and determine the most effective therapeutic approach. The study confirms an elevated level of resistance to clarithromycin, metronidazole, and levofloxacin in Italy. In addition, our results show a satisfactory eradication rate for a bismuth-based regimen when used as first- or second-line treatment. Naive patients are also successfully treated with clarithromycin-based quadruple therapies. Considering the good results of bismuth-based therapy as recovery therapy, this argues for the potential use of clarithromycin quadruple therapy as a first-line treatment.